Quantitative proteomics of epigenetic histone modifications in MCF-7 cells under estradiol stimulation. Issue 4 (18th January 2021) - Hu, Yechen; Jiang, Hao; Zhao, Baofeng; Yang, Kaiguang; Liang, Zhen; Zhang, Lihua; Zhang, Yukui
Abstract : SILAC-based quantitative proteomics strategy deciphers the mechanism of epigenetic regulation for breast cancer cell under estradiol stimulation. Abstract : Estrogen exposure has already been considered to be associated with tumorigenesis and breast cancer progression. To study the epigenetic regulation mechanism in MCF-7 cells under estrogen exposure, which normally results in cell proliferation and malignancy, a stable isotope labeling of amino acid (SILAC) based quantitative proteomics strategy was used to analyse histone post-translational modifications (PTMs) and protein differential expressions. In total, we have unambiguously identified 49 histone variants and quantified 42 of them, in which two differentially expressed proteins were found to be associated with breast cancers. Through the quantitative analysis of 470 histone peptides with a combination of different PTM types, including methylation (mono-, di-, and tri-), acetylation and phosphorylation, 150 of them were found to be differentially expressed. Through the biological analysis of the quantification results of both histone PTMs and proteins in MCF-7 cells, we found that (1) the histone variants H10 and H2AV have an effect on the adjustment of the nucleosome or chromatin structure and activate target genes; (2) after estrogen receptor (ER) activation by estrogen, the recruitment of histone acetyltransferase KAT7 might affect the acetylation at the N terminal of H4 (K5, K8 and K12) and also result in cross-talk between different acetylation sites; (3) different expression of histone deacetylase HDAC2 and its nucleo-cytoplasmic transportation process is important in the regulation of histone acetylation in MCF-7 cells under estrogen exposure.